Anti-solvent precipitation for the preparation of nobiletin nano-particles under ultrasonication-cis/reverse homogenization - Xiaonan Zhang; Tianqi Guo; Xiongjun Liu; Wei Kuang; Yuping Zhong; Manmin Zhang; Yan Huang; Zhiwei Liu (Ultrasonics Sonochemistry, 2023)
In order to address the issue of nobiletin's limited bioavailability, nobiletin nanoparticles (NNP) were created for the first time in this research employing an anti-solvent under ultrasonication-cis/reverse homogenization. Dimethyl sulfoxide (DMSO) was used as the solvent and deionized water as the anti-solvent to create the nobiletin solution. The optimal surfactant dose of surfactant dose of 0.43%; an ultrasonic period of 8.1 min, ultrasonic at a temperature of 64 °C and a solution concentration of 8.33 mg/mL, the method was optimized to obtain the minimum NNP diameter of 199.89 ± 0.02 nm. A dual optimization process of response surface PBD and BBD was used to minimize the size of HNP particles. Additionally, scanning electron microscopy revealed that the specific surface area of the NNP dramatically increased with the reduction of NNP particle size, and dissolving studies indicated the solubility and dissolution studies showed that NNP had substantially greater solubility and dissolution rates than raw nobiletin per unit time; as a result, the NNP produced by anti-solvent precipitation with a twofold homogenization system supported by ultrasound had a realistic potential for growth.